Methicillin and vancomycin resistant isolates of Staphylococcus aureus and Enterococcus faecalis recovered from bovine mastitis - KALATEH RAHMANI, H; AMIRI, P; EMANEINI, M; RAD, M; KHORAMIAN, B (Journal of the Hellenic Veterinary Medical Society, 2022)
Mastitis is the most costly disease in the dairy industry. Selecting the proper antibiotic treatment is beneficial for economic and avoids the emergence of antimicrobial resistance. The objective of the present study was to investigate the prevalence of methicillin and vancomycin resistant isolates of mastitis-causing Staphylococcus aureus and Enterococcus faecalis as a probable source of transferable vancomycin resistance to staphylococci. A total of sixty-one Staphylococcus aureus and eight Enterococcusfaecalis isolates were investigated for genotypic and phenotypic antimicrobial resistance.Presence of the mecA, vanA and vanBgenes were surveyed by PCR. The MIC (Minimum Inhibitory Concentration) of vancomycin was determined bybroth microdilution test for all the isolates.Moreover, the antibiotic resistance patterns of the isolates to the most common classes of antibiotics used in dairy cattle such as β-lactam, macrolides and tetracyclines were determinedusing the disk diffusion method. Among Staphylococcus aureus isolates, one MRSA (methicillin-resistant Staphylococcus aureus) isolate was detected while 47.5% of isolates were detected as multidrug-resistant. Furthermore, no phenotypic and genotypicvancomycin-resistance Staphylococcus aureus was found. Most of the Enterococcus faecalis isolates (6/8) showed high MIC for vancomycin (in the range of 128- 1024 μg/ml) and one vanA-type Enterococcus faecalis was observed. This study indicates thatsince the source of transferable resistance to vancomycin exists in dairy farms, there is a potential for emerging and spreading VRSA (vancomycin-resistant Staphylococcus aureus) in dairy cattle which is a risk to animal and human health.